HUBUNGAN PEKERJAAN IBU DAN PRAKTIK ASI EKSLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI KABUPATEN TIMOR TENGAH SELATAN - DJOGO, HERLIANA MONIKA AZI (STIKES Bethesda Yakkum, 2021)
The nutritional status of the community is a major reflection of the economic development and welfare of a country. One of the indicators to measure the progress of the Indonesian Healthy Program is the prevalence of stunting in children under five. East Nusa Tenggara Province, particularly Timor Tengah Selatan (TTS) District, is the only province and district in Indonesia that reports the highest incidence of stunting on a national scale. The purpose of this study was to determine the relationship between maternal occupation and exclusive breastfeeding practices with the incidence of stunting in children under five in TTS district. The design of this study was cross-sectional analytic. The population in this study were mothers and children aged 12-60 months in TTS Regency. The number of respondents in this study was 286 mothers and children. The sample was selected using purposive sampling technique. Data were collected using a questionnaire and anthropometric measurements (height and weight) according to WHO standards. The data collected were analyzed using bivariate analysis (chi square test). The results showed that 26.6% were stunted and 73.4% of children under five were not stunted, while 81.5% of mothers did not have a job and 68.2% of mothers did not exclusively breastfeed. The results of the Chi-Square test found that there was no significant relationship between maternal occupation and stunting with a p-value of 0.159 and there was a significant relationship between exclusive breastfeeding and the incidence of stunting with a p-value of 0.000.